This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
3 x + 1 6 = x − 3 6 ( x + 1 ) 2 = ( x − 3 ) 2 x 2 + 2 x + 1 = x 3 − 9 x 2 + 2 7 x − 2 7 x 3 − 1 0 x 2 + 2 5 x − 8 = 0 ( x − 7 ) ( x 2 − 3 x + 4 ) = 0 ( x 2 − 3 x + 4 ) > 0 so x=7
Thanks for the solution. How did you factor the expression x 3 − 1 0 x 2 + 2 5 x − 2 8 ?
should be -28 not -8
Problem Loading...
Note Loading...
Set Loading...
3 x + 1 3 y + 4 ( y + 4 ) 2 y 2 + 8 y + 1 6 y 3 − y 2 − 8 y − 1 6 ( y − 4 ) ( y 2 + 3 y + 4 ) y ⟹ x = x − 3 = y = y 3 = y 3 = 0 = 0 = 4 = 7 Let y = x − 3 Raise both sides by a power of 6 Note that y 2 + 3 y + 4 = 0 has no real root.